Comparison of Hypoglycemic and Antioxidant Activities of the Compounds Isolated from Ficus hispida Linn. and Ficus pomifera Wall - Nepram, Ashalata; Wangkheirakpam, Sujata; Laitonjam, Warjeet S. (Natural Products Journal, The, 2020)
Background: Traditional knowledge has been a legacy of the past to the present. Barks of Ficus hispida Linn. and leaves of Ficus pomifera Wall. (Moraceae) have been used traditionally for the treatment of diabetes in North-east India and many other places. As many drugs have been developed from traditional plants, the authors have taken up the plants for the study of hypoglycemic activity. Objective: To investigate the hypoglycemic activities of the triterpenoids isolated from the plants and their antioxidant activities. Methods: The bioactive compounds were determined by biochemical analysis, antioxidant activity using DPPH method. Hypoglycemic activity was detected using glucose tolerance test in normal rats and alloxan induced diabetic rats with Gliclazide as standard. Results: The biochemicals and trace elements were present in appreciable amounts. Triterpenoids, (1-5), from F. pomifera and 19-hydroxyphlogacantholide (6), 3-O-[ß-D-glucopyranosyl-(1’→2’)-α- L-rhamnopyranosyl-phlogacanthoside] (7) and galanolactone (8) along with stigmasterol (9), stigmasta- 5,22-dien-7-on-3ß-ol (10), 5-(decahydro-1,1,4a-trimethyl-6-methylene-5-yl)-3-methylpent-2- enal (11), stigmasterol glucoside (12) and stigmast-4-en-3-one (13) from F. hispida Linn., respectively, were isolated. The different extracts of the barks and leaves of these plants along with the isolated compounds had antioxidant and hyploglycemic activities. Conclusion: The five triterpenoids (1-5) were isolated from the methanol extract of the leaves of F. pomifera, and compounds (6-13) were isolated from the chloroform extract of the barks of F. hispida. Methanol extract of the leaves of F. pomifera and the chloroform extract of the barks of F. hispida; compounds (1-13) isolated from these two plants reduced DPPH free radicals in a concentrationdependent manner. It was also observed that the methanol and chloroform extracts of the plants, F. pomifera and F. hispida respectively, and the compounds (1, 6 & 7) exhibited anti-diabetic properties and also caused a highly significant reduction in the blood glucose levels of normal rats.
Keywords: ficus species